S20. LIFETIME PSYCHOPATHOLOGY IN CHILD AND ADOLESCENT OFFSPRING OF PARENTS DIAGNOSED WITH SCHIZOPHRENIA OR BIPOLAR DISORDER. (18th May 2020) - De la Serna, Elena; Ilzarbe, Daniel; Sugranyes, Gisela; Baeza, Inmaculada; Moreno, Dolores; Rodríguez, Elisa; Espliego, Ana; Ayora, Miriam; Romero, Soledad; Castro-Fornieles, Josefina
Abstract: Background: Having one parent diagnosed with a severe mental disorder is considered one of the main risk factors for developing that disorder in adulthood and it also increases the risk of a wide range of mental disorders in the offspring from early childhood and adolescence. The aim of this study is to analyze the prevalence of several psychopathological diagnoses, the presence of prodromal symptoms and global functioning in schizophrenia offspring (SZoff) or bipolar offspring (BDoff) compared to community control offspring (CCoff) at baseline and 2-year follow-up. Methods: 41 SZoff, 97 BDoff and 107 CCoff between 7 and 17 years were included. Clinical assessment consisted of a clinical evaluation using the following instruments: structured interview KSADS-PL or SCID-I, semi-structured Interview for Prodromal Syndromes (SIPS) and the Children's Global Assessment Scale (CGAS). To test between-group differences in DSM-IV diagnoses multilevel mixed-effect logistic regression models (categorical variables) or linear (continuous variables) regression models were conducted with group (SZoff, BDoff and CCoff), time (baseline or 2-year follow-up), interaction time x group, age, gender and socio-economic status as fixed variables. Results: Significant differences between groups were found in any lifetime axis I disorder (F=8.720; p<0.001), mood disorders (F=4.774; p=0.009), anxiety disorders (F=4.368; p=0.013), ADHD (F=21.593; p<0.001), disruptive behavioral disorders (F=10.788; p<0.001) and comorbidity (F=5.588; P=0.004). Significant differences between groups were also found in the positive (F=6.088; p=0.003), negative (F=4.423; p=0.015), disorganized (F=3.866; p=0.024) and total (F=6.394; p= 0.002) sub-scales of the SOPS and CGAS (F=11.613;p<0.001). Interestingly, mood disorders were more prevalent in BDoff and disruptive disorders were more prevalent in SZoff. Prodromal symptoms were higher in SZoff compared to CCoff, while the BPoff group showed an intermediate pattern. Finally, global functioning was lower in the SZoff group compared to BDoff and CCoff. Discussion: Screening patients' children is clinically relevant since, as a group, they have an elevated risk of developing a psychiatric disorder and of experiencing their first symptoms during childhood and adolescence.